Spatiotemporal Patterns and Physical Drivers of Satellite-derived Chlorophyll-a in the Aegean Sea - Anthi Koutsaniti; Manos Potiris; Yannis Androulidakis; Vassilis Zervakis; Elina Tragou (Thalassas: An International Journal of Marine Sciences, 2026)
Chlorophyll-a is widely used as an indicator of phytoplankton biomass and primary productivity in the Aegean Sea, with direct implications for marine ecosystem functioning. However, the connection of its variability to physical drivers in the region remain relatively understudied. This study investigates the interannual variability and long-term trends of sea surface chlorophyll-a in the Aegean Sea over 1998–2022 and their relation to physical forcing mechanisms (Black Sea water inflow, sea surface temperature, mixed layer depth, and wind). Atmospheric and oceanic forcing variables were obtained from reanalysis and satellite products. Seasonal dynamics dominate chlorophyll-a variability, with peak values in winter–early spring under deep mixing and minima in summer when strong stratification prevails. Spatial patterns reveal a pronounced north–south gradient, highlighting the influence of the Black Sea Water inflow. No statistically significant long-term trend was detected at the basin scale, however, statistically significant negative trends were observed during the last decade, after 2010. The analysis separates seasonal and non-seasonal variability, linking intra- and interannual fluctuations to both large-scale physical processes and episodic local events. The variability of the Black Sea Water inflow is reflected in the sea level differences between Bosporus (Black Sea entrance) and Dardanelles (Aegean exit). The inflow variability is directly associated with non-seasonal chlorophyll fluctuations, emphasizing the role of horizontal water exchanges in the fertilization of the Aegean Sea and the regional phytoplankton dynamics.